La lúdica como estrategia pedagógica para mejorar la convivencia escolar (2021)
The present research aims to propose pedagogical strategies from the ludic point of view to strengthen coexistence in fifth-year students of the María Mazzarello Mixed Educational Institution. Understanding school coexistence is an interrelational process that occurs from an interpersonal and collective dimension. This study uses as a study methodology a qualitative approach through an interpretive paradigm that seeks through participant observation and the application of a questionnaire designed for students and teachers to recognize the problems of school coexistence. Resulting in a perception of correct school coexistence, being clear about the concepts and the different factors that generate positive and negative environments within the school environment. Finally, it seeks to propose playful strategies to solve the problems of coexistence among students.